2021
DOI: 10.3390/medicina57020161
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Influence of Psoriasis and Sport

Abstract: The link between psoriasis and sport is a controversial issue. The topic has been poorly investigated, and nowadays there are many unsolved questions, dealing with the role of psoriasis in influencing the sporting habits of patients and, vice versa, the impact of sport activity on course, severity and extent of the disease, with particular regard to the indirect benefits on cardiovascular risk and metabolic syndrome. Moreover, the role of physical activity on patients’ quality of life and the potential limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In terms of physical activity, a properly tailored exercise plan in the Ps population has been proven to alleviate symptoms and reduce the risk of cardiometabolic diseases, which are significantly caused by low levels of physical activity. Moreover, this relationship is also observed among patients with a family history of Ps [60].…”
Section: Prevention Of Cardiovascular Eventsmentioning
confidence: 61%
“…In terms of physical activity, a properly tailored exercise plan in the Ps population has been proven to alleviate symptoms and reduce the risk of cardiometabolic diseases, which are significantly caused by low levels of physical activity. Moreover, this relationship is also observed among patients with a family history of Ps [60].…”
Section: Prevention Of Cardiovascular Eventsmentioning
confidence: 61%
“…Psoriasis has been found to be significantly less common in sportive subjects compared to controls. In addition, the number of subjects performing sport activities is significantly lower among psoriatic patients 9 …”
Section: Resultsmentioning
confidence: 99%
“…Physical activity is reported to be positively associated with improvement of psoriasis, as well as with that of cardiovascular, metabolic, and psychological comorbidities 9 . A 2019 Cochrane review confirmed that physical activity, along with weight loss, should be considered a standard accompanying treatment, by reducing the oxidative stress and PASI score, especially in over‐weight and obese patients receiving biologics or oral/traditional treatments 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations